Comparative Evaluation of Atorvastatin 20 mg versus 40 mg in the Management of Primary Hypercholesterolemia - GANJERA, MOHAMMAD AKHTAR NAWAZ; KHAN, M. ZAHID HAMEED; HAIDER, SAJJAD; SOUSA, MATHEUS SANTOS DE (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Atorvastatin, a commonly prescribed statin, plays a central role in lowering low-density lipoprotein cholesterol (LDL-C) in patients with hypercholesterolemia. While the 20 mg and 40 mg doses are frequently used in clinical practice, comparative real-world data on their lipid-lowering efficacy and tolerability remains limited in the Pakistani population. Objective: To evaluate and compare the efficacy and safety of Atorvastatin 20 mg versus 40 mg in managing primary hypercholesterolemia in adult patients at a tertiary care hospital in Lahore. Methodology: This prospective, comparative clinical study was conducted at Jinnah Hospital, Lahore, from March 2023 to December 2023. A total of 100 adult patients diagnosed with primary hypercholesterolemia were enrolled and randomly assigned into two groups: Group A (n=50) received Atorvastatin 20 mg once daily, and Group B (n=50) received Atorvastatin 40 mg once daily. Baseline and 12-week follow-up lipid profiles (LDL-C, total cholesterol, HDL-C, and triglycerides) were recorded. Adverse effects and liver enzyme levels were monitored throughout the study. Results: At the end of 12 weeks, Group B (40 mg) showed a statistically significant greater reduction in LDL-C and total cholesterol levels compared to Group A (20 mg) (p<0.05). HDL-C improved in both groups, while triglyceride reduction was more prominent in the higher dose group. No serious adverse events were reported; mild elevations in liver enzymes were noted in 4% of patients in Group B. Conclusion: Atorvastatin 40 mg demonstrates superior lipid-lowering efficacy over 20 mg without a substantial increase in adverse effects, supporting its use in patients with higher cardiovascular risk profiles.